Effect of Sb substitution on the topological surface states in Bi2Se3 single crystals: a magneto-transport study. (7th February 2017) - Devidas, T R; Amaladass, E P; Sharma, Shilpam; Mani, Awadhesh; Rajaraman, R; Sundar, C S; Bharathi, A
Abstract: Magneto-transport measurements have been carried out on Bi2−x Sbx Se3 (x = 0, 0.05, 0.1, 0.3, 0.5) single crystals at 4.2 K temperature in the magnetic field range of −15 T to 15 T. Shubnikov–de Haas (SdH) oscillations of 2D nature were observed in samples with Sb concentration upto x = 0.3. The analyses of SdH oscillations observed in magneto-resistance data using Lifshitz–Kosevich equation reveal a systematic decrease in the Fermi surface area with Sb substitution. The Berry phase obtained from the Landau level fan diagram suggests the occurrence of 2D oscillations arising from a topological surface state (TSS) for Sb concentrations of x = 0, 0.05 and 0.1; while 2D oscillation seen at higher Sb concentration is attributed to surface 2D electron gas consequent to downward band bending.